University Malaya Medical Centre (UMMC) Service Quality: A Pilot Study on Transformational Leadership and Empathy - Anantha Raj A. Arokiasamy (Research and Education Development (READ) Institute collaborate with Faculty of Education and Teacher Training of IAIN Palopo, 2020)
This pilot study observed the correlation between transformational leadership and a healthcare service provider's service quality. The research used two sets of cross-sectional questionnaire surveys designed to measure the Consumer Assessment of Healthcare Providers and Systems and a Leadership Inventory Index of the services rendered by the University Malaya Medical Centre (UMMC) to their patients to classify the quality of services delivered to patients at UMMC. The results emphasized a significant correlation between transformational leadership and empathy but no significant relationship between leadership effectiveness and service quality because of a lack of consensus and empirical support around which leadership types are significant. Transformational leadership has empirical support and is principles-based, relationship-oriented, intuitively appealing, and potentially “transformative. The study further stressed that the patients were pleased with the services rendered by UMMC staff. Also, additional education for physicians and physicians in training in transformational leadership is warranted.